Cerebrospinal fluid enolase isoenzymes and neurotoxicity in early treatment of lymphoblastic leukaemia. Issue 3 (March 1984) - Royds, J A; Lilleyman, J S; Timperley, W R; Taylor, C B
Abstract : Serial measurements of enolase in the cerebrospinal fluid were made in 19 children with lymphoblastic leukaemia undergoing their first 6 weeks of antineoplastic treatment. The neurone-specific gamma enolase value rose appreciably in nearly all patients during the first two weeks of treatment, which comprised chemotherapy only, but the mean values for this isoenzyme failed to show any further rise during the subsequent cranial irradiation. In contrast the alpha enolase value, which is derived predominantly from glial tissue, rose progressively to attain its highest value during radiotherapy. A consideration of the likely rate of clearance of gamma enolase from the cerebrospinal fluid and the time sequence of administration of the several chemotherapeutic agents in UKALL VIII suggests that asparaginase may be the main causative agent in the rise of this marker of neuronal damage.